Perbedaan Beban Kognitif pada Penggunaan Kata Sandi Berbasis Pola Garis dan Angka - Paulus Insap Santosa (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
Most applications require users to enter a password in order to use those applications. One type of the passwords used on smartphones is based on certain line pattern. The pattern of lines that make up the password is essentially an image similar to a sequence of numbers arranged in a particular order. Just when users need to memorize a series of numbers, "memorizing" the line pattern also gives cognitive load to certain level. This study observed the cognitive load experienced by users when they were using line pattern-based password as compared to numeric-based password. The research method employed in this study was a scenario-based experiment followed by a survey to self-report the cognitive load experienced by the user after they run the scenario. Cognitive load experienced by users were reported by users themselves. The subjects of the study were 67 undergraduate and master students. They were voluntarily participated in this research. The result obtained from this study indicated that the cognitive load experienced by users when they used the pattern of the line based password was smaller than the number-based password.